HARMONIOUS SOCIAL ENTREPRENEURSHIP: A BUSINESS INNOVATION MODEL FOR EMPOWERING INDONESIAN COMMUNITIES THROUGH RELIGIOUS ORGANIZATIONS - Waraney Alfonsus Matthew Punuh; Hani Sirine (Jurnal Manajemen dan Kewirausahaan, 2024)
Religious organizations possessed significant potential for community empowerment through social entrepreneurship practices. Although social entrepreneurship had emerged as a strategy within religious institutions to bolster congregational and community economies, it had yet to garner adequate attention. This study aimed to identify social entrepreneurship implementations, explore challenges, and formulate a suitable social entrepreneurship model within the context of religious organizations. The research was conducted within a religious organization in North Sulawesi, Indonesia. The findings suggested that achieving harmonious social entrepreneurship in Indonesia required an inclusive, collaborative stakeholder approach and increased NGO involvement through mentoring roles in entrepreneurial activities. Through a business innovation model integrated into religious organizations, community well-being could be achieved by synergizing entrepreneurship and spiritual values.